The ethics of pediatric research - Wendler, David (New York ; Oxford : Oxford University Press, 2010)
David Wendler offers an original justification for pediatric research based on an in-depth analysis of when it is in our interests to help others. It will be of interest primarily to scholars in pediatric ethics and clinical research ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pediatrics -- Research -- Moral and ethical aspects; Medical ethics; Research -- Moral and ethical aspects